The Effect of Problem Based Learning Model Implementation Toward Students’ Learning Competencies at SMPN 2 Padang Panjang - Wulan Rahmadani; Rahmawati D. Rahmawati D.; Sa'diatul Fuadiyah; Ristiono Ristiono (ATRIUM PENDIDIKAN BIOLOGI, 2019)
The low learning competencies of students is caused by several problems found during  learning process, one of them  is teacher centered. Learning through  this way causes students to be inactive. One of the efforts made to improve student learning competencies is to apply a Problem Based Learning model. Learning with a problem based learning model requires students to be active. The purpose of this study was to determine the effect of applying the Problem Based Learning model to the learning competencies of Class VIII at SMPN 2 Padang Panjang.The type of this research is an experimental study with a control group posttest only design. The study population is  all students of Class VIII SMPN 2 Padang Panjang. Sampling was done using purposive sampling technique, which was chosen as the research sample was Class VIII D as the experimental class and Class VIII E as the control class. The instruments used were in the form of posttest questions for knowledge competencies, observation sheets for attitude and skills competencies. The data analysis technique used in this study is the normality test, homogeneity test and hypothesis testing with t-test.Result of hypothesis in both class sample, found that class which use Problem Based Learning model have possitive effect to student learning competencies of Class VIII SMPN 2 Padang Panjang such asknowledge, attitude and skill competencies.